Analisis Intrinsic Value Dan Market Value Pada Event China Market Crash 2015 (Studi Kasus Pada Industrial And Commercial Bank Of China Ltd) - Silaban, Daniel Peterson (Universitas Sam Ratulangi, 2016)
The purpose of this research is to understand the changes that occurred on intrinsic value and market value after the emergence of market crash, also to analyze both impact and its form that exist between market crash and both valuation methods. The research results show that: significant changes do occur in intrinsic value and market value after the market crash. The results also show that market crash gives a significant impact towards both intrinsic value and market value. The significant impact of market crash causes the heavy downturn in both market intrinsic value and market value Keywords: market crash, intrinsic value, market value